Driving Night Travel Decisions with Local Wisdom Product Offers to Enhance the Travel Experience - Trenggono, Trenggono; Marhendi, Mengku; Listyorini, Haniek (Riviera Publishing, 2022)
Introduction: Big cities in Indonesia intensify night tourism activities in their respective cities to increase tourist visits and provide a different atmosphere for the experience. This study aims firstly to examine how the influence of local wisdom product offerings typical of a destination on the decisions of night tourism entrepreneurs, secondly to explore the impact of local wisdom products on the travel experience, and thirdly to examine the effect of night tourism decisions. Method: To test this model, 100 tourist respondents were taken at several points of night tourism activities in Semarang City; Then, the data was processed using SEM PLS. Result: The partial hypothesis test shows the value of t - independent statistical variable of local wisdom product against the dependent variable of the travel experience of 1,449 < 1.96 and the importance of t - independent statistical variable of local wisdom product to the intervening variable of night travel decision of 15,336 > 1.96. Simultaneous hypothesis testing showed the importance of t - independent statistical variables of local wisdom products against dependent variables of travel experience through intervening variables of night travel decisions of 7.289 > 1.96. Conclusion: The first study shows that local wisdom products influence the decision to travel to the city of Semarang at night. Second, the development of local wisdom also influences the travel experience—a distinctive art. The three decisions of the following night tour affect the experience of travelling at night in the city of Semarang. Fourth, the decision to travel at night is a variable that mediates the travel experience.